The impact of inventory management practice on firms' competitiveness and organizational performance: Empirical evidence from micro and small enterprises in Ethiopia - Daniel Atnafu; Assefa Balda (Cogent Business & Management, 2018)
This study aimed to empirically examine the impact of inventory management practice on firms' competitiveness and organizational performance. Data for the study were collected from 188 micro and small enterprises (MSEs) operating in the manufacturing sub-sector and the relationships and hypothesis proposed in the conceptual framework were tested using structural equation modeling (SEM). The results indicate that higher levels of inventory management practice can lead to an enhanced competitive advantage and improved organizational performance. Also, competitive advantage can have a direct, positive impact on organizational performance. Therefore, it is recommended that policy makers, universities, NGOs and any concerned party who are engaged in supporting of MSEs need to work on providing the necessary training and resource to promote the inventory management practice of MSEs which will result in increasing their competitiveness and organizational performance. That would enhance their contribution to the economic development of the country. Note that, the conclusion obtained from this study may not be used to generalize to large and medium scale as well as overall sectors since its focus is only from the MSEs' manufacturing sub-sector points of view.
Keywords: 650